A general datalog-based framework for tractable query answering over ontologies. - Calì, A; Gottlob, G; Lukasiewicz, T (ACM, 2009)
In this paper, we introduce a family of expressive extensions of Datalog, called Datalog±, as a new paradigm for query answering over ontologies. The Datalog± family admits existentially quantified variables in rule heads, and has suitable restrictions to ensure highly efficient ontology querying. We show in particular that Datalog± generalizes the DL-Lite family of tractable description logics, which are the most common tractable ontology languages in the context of the Semantic Web and databases. We also show how stratified negation can be added to Datalog± while keeping ontology querying tractable. Furthermore, the Datalog± family is of interest in its own right and can, moreover, be used in various contexts such as data integration and data exchange. Copyright 2009 ACM.